Building A Moral Generation: Habituation Strategies in the Internalization of Religious Character at SDIT Darul Fikri Balangan - Miftahul Fahmi; Jasiah Jasiah (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
The purpose of the research conducted by the researcher is: to analyze the cultivation of religious character through the habituation method in students of SDIT Darul Fikri Balangan, as a role model for other schools in cultivating religious character to form individuals who have knowledge and religious character. This study uses a qualitative method. The results of the study show that the cultivation of religious character is carried out in an integrated manner in various cultures and daily activities in schools, which involves habituation methods. These activities include: Musyafahah (shaking hands with teachers in the morning), as a form of respect and the formation of a polite attitude. Greetings when entering class and prayers before and after learning, instill Islamic manners in every learning activity. The implementation of dhuha prayers is routine to get used to sunnah worship. The morning assembly, which includes hadith memorization and prayer activities, is a way of instilling religious values through understanding and practice. Muroja'ah memorizes the Qur'an, keeping students' memorization firm and internalized. Reciting the Qur'an with the Ummi method, supporting the ability to read the Qur'an well and correctly. Tahfidz Al-Qur'an Juz 30 and 29, to bring students closer to the Qur'an and build the personality of the Qur'an. Dzuhur and ashar prayers in congregation, training discipline, togetherness, and commitment to the obligation of worship. This habituation method applied is effective in instilling religious character, because it is carried out consistently and integrated in the daily activities of students at SDIT Darul Fikri Balangan. This shows that habituation is one of the strategic approaches in religion-based character education.